Testosterone Treatment and Cardiovascular and Venous Thromboembolism Risk: What is 'New'?. (August 2017) - Corona, G; Dicuio, M; Rastrelli, G; Maseroli, E; Lotti, F; Sforza, A; Maggi, M
In men, testosterone (T) production declines as a function of ageing. Late-onset hypogonadism (LOH) is the most commonly used term to indicate this age-related condition. In LOH, the relative clinical significance and the potential benefit of testosterone treatment (TTh) are still the subject of strong criticisms in the scientific community. The debate is further complicated by the recent position statement of the US Food and Drug Administration (FDA) emphasizing that, in LOH, the benefits and safety of TTh have not been fully established. Hence, the FDA required a labeling change to inform patients about a possible increased cardiovascular (CV) risk of TTh. Similar considerations were previously released by the FDA and by Health Canada concerning a TTh-related venous thromboembolism (VTE) risk. In this review, we will summarize the available evidence concerning a possible link among TTh and CV and VTE risks. For this purpose, data derived from epidemiological studies analyzing relationships between the aforementioned risks and endogenous T levels will be analyzed. In addition, evidence deriving from interventional studies including pharmacoepidemiological and placebo-controlled randomized controlled trials (RCTs) will be examined. Our analysis shows that available data do not support an increased CV risk related to TTh. Similar considerations can be drawn for the relationship between TTh and VTE. The previously reported cases of TTh-related VTE were frequently related to a previously undiagnosed thrombophilia-hypofibrinolysis status. Hence, an anamnestic screening for thrombophilia before starting TTh is recommended, just as it is for the use of oral contraceptives.